Quality of Service - صلاح الدين, أحمد; عبد الهادي, محمد عثمان (Gezira Journal of Engineering and Applied Sciences, 2018)
The quality of services concepts provided by computer network is a new computer technology at the current time   . In the past, there was  a slow Internet access in dealing with sites and slow to move files from one location to another, but now requires  characterized services by high speed and efficiency in audio, image and we must a avoidance  users complaints so as to complete all of these services, we find that the quality of service in the network leads to this purposes, according to its ability to send and reception of data, and we take in this comparison sheet between the quality of services provided algorithms over the network, so we have comparison between algorithms FIFO, PQ, CQ, CQ with LLQ, WFQ, WFQ with LLQ and measure the behavior and characteristics of these algorithms such as delays ( distributing packets), and the change in the delay and the amount of information being processed in a specific time period (distribution rate), and the results that have been accessed through comparison between them is that the best algorithm enrolled and settled the arrival of the number of bytes is Priority queuing algorithm followed by CQ then CQ with LLQ and WFQ then WFQ with LLQ Finally FIFO, where I took these results based on the  all curves of these  algorithms  individual state.                                 Also we found   that the transfer of packets always have a high sensitivity,  loss  the sound ,so quality of service technology is very important to activate and use in processing delays and prevent crowded in  network and the quality of the audio recordings, video recordings, and prevent the loss of packets problems during transmission.